ACHIEVING EXCELLENCE: THE INTERSECTION OF TALENT MANAGEMENT AND ORGANIZATIONAL EFFECTIVENESS - Tamunomiebi, Miebaka Dagogo (Journal of Healthcare Management and Administration (JHMA), 2022)
In today’s rapidly changing and competitive business landscape, organizations face numerous challenges in achieving their predetermined goals and objectives. To ensure survival and success, organizations must strive to be effective in all aspects of their operations. This effectiveness is measured by the organization’s ability to achieve its goals, acquire necessary resources, and maintain high performance levels while fostering employee commitment. Conversely, ineffective organizations often struggle to meet their goals, acquire resources, and experience job dissatisfaction, leading to negative outcomes such as absenteeism, high turnover rates, and decreased job performance. To address these challenges, organizations are increasingly focusing on talent management as a strategic approach to enhance organizational effectiveness. By attracting and retaining highly talented individuals, organizations can not only achieve their corporate goals but also establish and maintain a positive relationship with the business environment, ensuring access to necessary resources and sustaining a competitive edge. Talent management encompasses various dimensions and offers benefits for both the organization and its employees. This paper aims to explore the relationship between talent management and organizational effectiveness. The concept of talent management will be examined, including its dimensions and the advantages it offers to organizations and employees. Additionally, the concept of organizational effectiveness will be discussed, highlighting its measures of goal accomplishment, resource acquisition, and internal processes. By exploring these concepts, the paper aims to demonstrate how talent management can realistically contribute to organizational effectiveness